The Relationship between Knowledge, Attitude, and Family Support and the Success of Tuberculosis Preventive Treatment among Household Contacts of Drug-Sensitive TB Patients - I Nyoman Teguh Apriana; Sastrawan (Postgraduate, University of Mataram, 2026)
Tuberculosis (TB) remains a serious health problem in Indonesia, particularly in the West Nusa Tenggara region. Tuberculosis Preventive Treatment (TPT) for household contacts of drug-sensitive (DS) TB patients is a key strategy for TB elimination; however, TPT coverage at Puskesmas Pelangan, West Lombok Regency, remains at only 25.25%, far below the national target. This study aimed to describe knowledge, attitude, family support, and TPT success, and to analyze the relationship between each of these variables and the success of TPT administration among household contacts of DS-TB patients. A quantitative study with a cross-sectional design was conducted in 2025 in the working area of Puskesmas Pelangan, West Lombok Regency, using the TB program database for the 2024–2025 period. Samples were taken purposively from all registered household contacts of DS-TB patients. Data were collected through a structured questionnaire and a review of the Puskesmas Pelangan TB program records. Bivariate analysis used the Chi-square test and Fisher's Exact test, with a significance level of p < 0.05. Puskesmas Pelangan's TPT achievement (25.25%) ranked second highest in West Lombok after Sesela (61.62%), yet remained very low compared with the national standard. Most respondents had poor knowledge (62.5%), a negative attitude toward TPT (58.3%), and low family support (53.8%). Bivariate analysis showed significant relationships between knowledge (p = 0.012), attitude (p = 0.008), and family support (p = 0.003) with TPT success. Knowledge, attitude, and family support were each independently and significantly associated with TPT success. Family support was the most dominant factor. Interventions to strengthen family capacity and community education are needed to improve TPT achievement in the working area of Puskesmas Pelangan.